Progress in silicon microwire solar cells. Issue 11 (4th March 2020) - Um, Han-Don; Lee, Kangmin; Hwang, Inchan; Park, Jeonghwan; Choi, Deokjae; Kim, Namwoo; Kim, Hyungwoo; Seo, Kwanyong
Abstract : This review introduces recent progress in silicon microwire solar cells, including the strategies toward achieving low-cost and high-efficiency silicon solar cells. Abstract : Silicon microwires are very promising candidates for next-generation solar cells. Si microwires achieve strong broadband light absorption, acting as an antireflection coating layer. In addition to superior optical properties, Si microwires can effectively separate and collect photocarriers at the radial junction owing to a short diffusion length (equal to the microwire radius). This factor can relax the requirement for high-quality materials, enabling a reduction in the cost of producing solar cells. In this report, we review recent progress in vertically aligned Si microwire solar cells with reference to (1) optimized microwire structures to enhance light absorption, (2) uniform radial junctions for effective carrier separation, (3) minimization of surface recombination through surface treatments, and (4) fine metal electrodes for efficient carrier collection. In addition, we present studies on flexible crystalline Si solar cells that use mechanically flexible Si microwires. Furthermore, based on each fabrication process, we discuss the challenges related to the realization of high-efficiency Si microwire solar cells.